2015
DOI: 10.1103/physrevd.92.104013
|View full text |Cite
|
Sign up to set email alerts
|

Connections and geodesics in the space of metrics

Abstract: We argue that the exponential relation gµν =ḡµρ e h ρ ν is the most natural metric parametrization since it describes geodesics that follow from the basic structure of the space of metrics. The corresponding connection is derived, and its relation to the Levi-Civita connection and the VilkoviskyDeWitt connection is discussed. We address the impact of this geometric formalism on quantum gravity applications. In particular, the exponential parametrization is appropriate for constructing covariant quantities like… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 52 publications
1
53
0
Order By: Relevance
“…The divergences also agree, in d = 4 and in the EH limit, with earlier calculations in general gauges [29,[45][46][47][48]. For further discussions on the use of the exponential parametrization see [27,[49][50][51][52][53][54].…”
Section: Discussionsupporting
confidence: 82%
“…The divergences also agree, in d = 4 and in the EH limit, with earlier calculations in general gauges [29,[45][46][47][48]. For further discussions on the use of the exponential parametrization see [27,[49][50][51][52][53][54].…”
Section: Discussionsupporting
confidence: 82%
“…Only then it is ensured that all metrics parametrized this way satisfy the signature and nondegeneracy constraint. It can be shown that there is a canonical connection on F adjusted to this constraint, and that the resulting geodesics are parametrized precisely by the exponential relation g µν =ḡ µρ (e h ) ρ ν with a symmetric tensor field h µν [59]. This explains the special status of the exponential parametrization.…”
Section: Jhep02(2016)167mentioning
confidence: 92%
“…Since the set of nondegenerate metrics with fixed signature forms a nonempty open subset in the space of all covariant symmetric 2-tensor fields [59], there is no a priori reason to expect that it has vanishing measure, and so this question has no obvious answer. It is known, however, that "sufficiently different" choices will lead to inequivalent theories [79].…”
Section: Different Universality Classes?mentioning
confidence: 99%
See 2 more Smart Citations